2020
DOI: 10.3390/molecules25051130
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Sphingolipid Metabolism and Its Implications for the Pathogenesis of Psoriasis

Abstract: Sphingolipids (SLs), which have structural and biological responsibilities in the human epidermis, are importantly involved in the maintenance of the skin barrier and regulate cellular processes, such as the proliferation, differentiation and apoptosis of keratinocytes (KCs). As many dermatologic diseases, including psoriasis (PsO), intricately characterized by perturbations in these cellular processes, are associated with altered composition and unbalanced metabolism of epidermal SLs, more education to precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 124 publications
(150 reference statements)
0
23
0
Order By: Relevance
“…In the presence of stress stimuli, sphingomyelin is broken down to ceramide and phosphocholine. This reaction is mediated by sphingomyelinase 29,30 . Undesired complex sphingolipids such as glycosphingolipids may be broken down in the acidic environment of lysosomes or late endosomes to ceramide 29 .…”
Section: ) Salvage Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of stress stimuli, sphingomyelin is broken down to ceramide and phosphocholine. This reaction is mediated by sphingomyelinase 29,30 . Undesired complex sphingolipids such as glycosphingolipids may be broken down in the acidic environment of lysosomes or late endosomes to ceramide 29 .…”
Section: ) Salvage Pathwaymentioning
confidence: 99%
“…This reaction is mediated by sphingomyelinase 29,30 . Undesired complex sphingolipids such as glycosphingolipids may be broken down in the acidic environment of lysosomes or late endosomes to ceramide 29 . Complex glycosphingolipids are degraded through sequential hydrolysis of terminal hydrophilic moieties by hydrolases, where glucose or galactose is removed by β-glucosidases or galactosidase, respectively, to produce ceramide.…”
Section: ) Salvage Pathwaymentioning
confidence: 99%
“…Moreover, it plays an important signaling role in epidermal barrier function and migration of endothelial cells protecting and maintaining vascular integrity. 10 Notably, up-regulation of S1P phosphatase 2 (SPP2) mRNA expression was identified in psoriatic lesions biopsy samples. 11 The impact of obesity on the circulating levels of sphigolipids was studied in a case control study and S1P higher concentrations were found in all psoriatic patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LPC is involved in inducing apoptosis and promoting reactive oxygen species production to enhance oxidative stress. [ 58 , 106 ]…”
Section: Role Of Metabolites In the Pathogenesis Of Psoriasismentioning
confidence: 99%
“…First, it induces DC apoptosis by downregulating survival signaling pathways, such as NF-κB and protein kinase B (PKB). [ 106 ] In addition, ceramides may participate in the induction of DC maturation and promote the production of major histocompatibility complex class I molecules and the secretion of proinflammatory cytokines, such as IL-12 and TNF-α. [ 107 ] Moreover, S1P has anti-inflammatory effects by reducing the production of IL-12 and IL-23 by the shared p40 subunit in DCs, thereby inhibiting DC crosstalk with activated keratinogenic cells.…”
Section: Role Of Metabolites In the Pathogenesis Of Psoriasismentioning
confidence: 99%